Percepetion on the importance of vocational training for elite judo coaches - Tavares Junior, Antonio Carlos (2018)
This paper aims to report what is the importance elite judo coaches give to vocational training, in order to plain, prescript and control the training process. The paper is using a qualitative approach, and can be classified as a multiple case study. Eight judo coaches have been intentionally selected to take part of the research. Interviews have been performed with the coaches in two different moments: the first part was structured and the second part was semi structured. This study sample was composed by young coaches (37.4±3.8 years), who have already conquer expressive results in their carriers. They all have physical education degrees, while six of them are post-graduated (four specialists and two masters). We could observe that, for this group, the vocational training has always been of essential importance in their carriers as sportive coaches.